A New Role for Extracellular Vesicles in Cardiac Tissue Engineering and Regenerative Medicine. Issue 11 (6th August 2021) - Wagner, Karl T.; Radisic, Milica
Abstract : Cardiovascular diseases are the leading cause of death worldwide. Discovering new therapies to treat heart disease requires improved understanding of cardiac physiology at a cellular level. Extracellular vesicles (EVs) are plasma membrane‐bound nano‐ and microparticles secreted by cells and known to play key roles in intercellular communication, often through transfer of biomolecular cargo. Advances in EV research have established techniques for EV isolation from tissue culture media or biofluids, as well as standards for quantitation and biomolecular characterization. EVs released by cardiac cells are known to be involved in regulating cardiac physiology as well as in the progression of myocardial diseases. Due to difficulty accessing the heart in vivo, advanced in vitro cardiac "tissues‐on‐a‐chip" have become a recent focus for studying EVs in the heart. These physiologically relevant models are producing new insight into the role of EVs in cardiac physiology and disease while providing a useful platform for screening novel EV‐based therapeutics for cardiac tissue regeneration post‐injury. Numerous hurdles have stalled the clinical translation of EV therapeutics for heart patients, but tissue‐on‐a‐chip models are playing an important role in bridging the translational gap, improving mechanistic understanding of EV signaling in cardiac physiology, disease, and repair. Abstract : Extracellular vesicles (EVs) are cell‐secreted nano and micro‐particles having important functions in intercellular communication and the progression of heart diseases. EVs harvested in the lab show significant promise as a regenerative therapeutic for the injured heart. 3D models of heart "tissue‐on‐a‐chip" represent promising platforms to advance understanding of cardiac EVs toward designing new therapies for heart patients.